Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch84
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of TTT Diagram for Alloy 718Plus®

Abstract: The phase evolution of Allvac® alloy 718Plus® has been determined experimentally via construction of time-temperaturetransformation (TTT) and continuous-cooling-transformation (CCT) curves based on identifying the various phases, their sizes and volume fractions along with distributions as they evolved during thermal treatment. The solution temperature range of interand intra-granular  phases and of have been characterized via detailed microstructural investigations. The phase solvus of alloy 718Plus det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 5 publications
3
22
0
Order By: Relevance
“…The XRD spectra ( Figure 5) demonstrate unambiguously the presence of stable η after 16 h, and a smaller amount of δ phase developing after 72 h. It should also be noted that our results regarding the presence of η are not necessarily inconsistent with other reports of the presence of δ phase alone in 718 ® Plus [11,12], as in these papers both thermo-mechanical histories and the heat treatments are different from the one performed in this study. Great care must be taken to distinguish the two structures, which have very similar diffraction characteristics.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The XRD spectra ( Figure 5) demonstrate unambiguously the presence of stable η after 16 h, and a smaller amount of δ phase developing after 72 h. It should also be noted that our results regarding the presence of η are not necessarily inconsistent with other reports of the presence of δ phase alone in 718 ® Plus [11,12], as in these papers both thermo-mechanical histories and the heat treatments are different from the one performed in this study. Great care must be taken to distinguish the two structures, which have very similar diffraction characteristics.…”
Section: Discussionsupporting
confidence: 48%
“…The grounding of aircraft in the USA resulting from the tragic events of the 11 September 2001 allowed researchers to evaluate the effect of air traffic on the regional and global climate. Travis et al [1] reported a significant anomaly of +1.1°C in the diurnal temperature range during the flight interruption (11)(12)(13)(14). Without legislative intervention and consortia between aerospace companies, the projected increase in air traffic will further augment the effect on climate on a global scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although early literature on 718Plus [5,7] reported 8 solvus temperatures as high as 1065 °C, obtained from thermodynamic calculations, the present result is in agreement with more recent studies, which placed the 8 solvus around 980 °C -1000 °C [28,30]. The exception is a study by Srinivasan et al [23], which indicates a solvus temperature between 1010 °C and 1071 °C, although after annealing times o f only 6 minutes. For heat treatments at 925 °C and 950 °C the etching revealed the presence o f spherical Y particles, indicating that the solvus temperature o f the Y phase is between 950 °C and 975 °C.…”
Section: Kinetics O F Secondary Phase Precipitationsupporting
confidence: 91%
“…The interest in alloy 718Plus has prompted the appearance of several studies tackling the same issue, although the information already available is naturally more limited. The precipitation kinetics of the strengthening phase y' has first been studied in terms of hardness [7,23] and later completed with TEM observations [23] and modeling simulations [5,24]. TTT diagrams of n/5 phase precipitation have been published both in solution-treated (strain free) [5,7] and forged [5,13,25] material.…”
Section: Introductionmentioning
confidence: 99%